Effect of ropivacaine scalp nerve block on postoperative recovery quality after craniotomy - LI Wenjing, LIAO Jinwen, HEI Ziqing, CAI Jun, XING Jibin (Xin yixue)
Objective To evaluate the effect of 0.5% ropivacaine for scalp nerve block on postoperative pain and recovery quality in craniotomy patients， and provide a reference for optimizing clinical anesthesia plans. Methods Sixty-six patients scheduled for craniotomy under general anesthesia were selected and randomly divided into ropivacaine group （R group） and control group （C group） in a 1∶1 ratio. The R group received bilateral scalp nerve blocks with 0.5% ropivacaine after anesthesia induction， while the C group was not treated. The primary outcome was the postoperative 6-hour Visual Analogue Scale （VAS） score. Secondary outcomes included VAS scores at 24， 48， and 72 hours postoperatively； remifentanil dosage during surgery； mean arterial pressure （MAP） and heart rate （HR） at key surgical time points， including before nailing， during nailing， before skin incision， during skin incision， before extubation， and after extubation； postoperative analgesic rescue rate； incidence of postoperative complications； incidence of postoperative nausea and vomiting， hypotension， fever， pneumonia， epilepsy， deep vein thrombosis， and pressure sores； time to first postoperative meal and ambulation； hospital stay length； and the scores of anxiety， depression， and sleep preoperatively and postoperative 24-hour. Results Sixty-one patients were finally included， with 30 in the R group and 31 in the C group. Compared to the C group， the R group had significantly lower VAS scores at 6 and 24 hours postoperatively （all P < 0.05）， but no significant difference at 48 and 72 hours （all P > 0.05）. The R group had lower remifentanil dosage （P < 0.05）， lower analgesic rescue rate （P <0.05）， lower MAP at three time points （before nailing， before skin incision， before extubation）， and lower HR during nailing （all P < 0.05）. The R group also had earlier time to first meal and ambulation， and shorter hospital stay （all P < 0.05）. No significant difference was found in postoperative nausea and vomiting， hypotension， fever， epilepsy， pneumonia， deep vein thrombosis， and pressure sores between the two groups （all P > 0.05）. The R group had lower anxiety and depression scores at 24 hours postoperatively compared to preoperatively （P < 0.05）， while the C group had higher Pittsburgh Sleep Quality Index （PSQI） scores （P < 0.05）. Conclusions Preoperative scalp nerve block with 0.5% ropivacaine can effectively relieve perioperative pain， reduce opioid use and cardiovascular stress response， and improve postoperative recovery quality in craniotomy patients， including anxiety， depression， time to first meal and ambulation， and hospital stay length， promoting the early rehabilitation of craniotomy patients.